High Fat Diet and Inflammation – Modulation of Haptoglobin Level in Rat Brain - Spagnuolo, Maria Stefania; Mollica, Maria Pina; Maresca, Bernardetta; Cavaliere, Gina; Cefaliello, Carolina; Trinchese, Giovanna; Scudiero, Rosaria; Crispino, Marianna; Cigliano, Luisa (Frontiers in Cellular Neuroscience, 2015)
Obesity and dietary fats are well known risk factors for the pathogenesis of neurodegenerative diseases. The analysis of specific markers, whose brain level can be affected by diet, might contribute to unveil the intersection between inflammation/obesity and neurodegeneration. Haptoglobin (Hpt) is an acute phase protein, which acts as antioxidant by binding free Haemoglobin (Hb), thus neutralizing its pro-oxidative action. We previously demonstrated that Hpt plays critical functions in brain, modulating cholesterol trafficking in neuroblastoma cell lines, beta-amyloid (Aβ) uptake by astrocyte, and limiting Aβ toxicity on these cells. A major aim of this study was to evaluate whether a long term (12 or 24 weeks) high-fat diet (HFD) influences Hpt and Hb expression in rat hippocampus. We also assessed the development of obesity-induced inflammation by measuring hippocampal level of TNF-alpha, and the extent of protein oxidation by titrating nitro-tyrosine (N-Tyr). Hpt concentration was lower (p<0.001) in hippocampus of HFD rats than in control animals, both in the 12 and in the 24 weeks fed groups. HFD was also associated in hippocampus with the increase of Hb level (p<0.01), inflammation and protein oxidative modification, as evidenced by the increase in the concentration of TNF-alpha and nitro-tyrosine. In fact, TNF-alpha concentration was higher in rats receiving HFD for 12 (p<0.01) or 24 weeks (p<0.001) compared to those receiving the control diet. N-Tyr concentration was more elevated in hippocampus of HFD than in control rats in both 12 weeks (p=0.04) and 24 weeks groups (p=0.01), and a positive correlation between Hb and N-Tyr concentration was found in each group. Finally, we found that the treatment of the human glioblastoma-astrocytoma cell line U-87 MG with cholesterol and fatty acids, such as palmitic and linoleic acid, significantly impairs (p<0.001) Hpt secretion in the extracellular compartment. We hypothesize that the HFD-dependent decrease of Hpt in hippocampus, as associated with Hb increase, might enhance the oxidative stress induced by free Hb. Altogether our data, identifying Hpt as a molecule modulated in the brain by dietary fats, may represent one of the first steps in the comprehension of the molecular mechanisms underlying the diet-related effects in the nervous